Holocene vegetation, fire and climate interactions on the westernmost fringe of the Mediterranean Basin - Morales-Molino, César; García-Antón, Mercedes; Postigo-Mijarra, José M; Morla, Carlos (Quaternary Science Reviews, 2013)
A new palaeoecological sequence from the western Iberian Central Range signiﬁcantly contributes to the knowledge on the Holocene vegetation dynamics in central Iberia. This sequence supports the existence of time-transgressive changes in the vegetation cover during the beginning of the Holocene over these central Iberian mountains, speciﬁcally the replacement of boreal birchepine forests with Mediterranean communities. Anthracological analyses also indicate the replacement of boreal pines (Pinus sylvestris) with Mediterranean ones (Pinus pinaster) during the early Holocene. The observed vegetation changes were generally synchronous with climatic phases previously reconstructed for the western Mediterranean region, and they suggest that the climatic trends were most similar to those recorded in the northern Mediterranean region and central Europe. Several cycles of secondary succession after ﬁre ending with the recovery of mature forest have been identiﬁed, which demonstrates that the vegetation of western Iberia was highly resilient to ﬁre disturbance. However, when the recurrence of ﬁre crossed a certain threshold, the original forests were not able to completely recover and shrublands and grasslands became dominant; this occurred approximately 5800e5400 cal yr BP. Afterwards, heathlands established as the dominant vegetation, which were maintained by frequent and severe wildﬁres most likely associated with human activities in a climatic framework that was less suitable for temperate trees. Finally, our palaeoecological record provides guidelines on how to manage protected areas in Mediterranean mountains of southwestern Europe, especially regarding the conservation and restoration of temperate communities that are threatened there such as birch stands.
Keywords: Betula; charcoal; Fire ecology; Forest management; Heathlands; macrofossils; pollen; Spain

Predicting heating values of lignocellulosics and carbonaceous materials from proximate analysis - Cordero, T; Marquez, F; Rodriguez-Mirasol, J; Rodriguez, J J (Fuel, 2001)
A simple equation based on proxymate analysis (volatile matter and fixed carbon contents) is presented which allows calculation of the higher heating value of lignocellulosic as well as the charcoals resulting from their carbonization. The equation has been tested with different lignocellulosic wastes and chars obtained from carbobization at different temperatures. Derivations from the experimental heating values fall in most cases below 2%. A comparison is presented with some equationsfrom the literature based on proximate, ultimate and chemical analysis data. As a general conclusion the equation proposed in this paper leads to comparableand in many cases more accurate predictions of heating valus and has the advantage of being applicable to a wide range of carbonaceous materials, requiring only a simple, rapid and cheap proximate analysis of the samples
Keywords: charcoal; heating value calculation; lignocellulosics

Predicting heating values of lignocellulosics and carbonaceous materials from proximate analysis - Cordero, T.; Marquez, F.; Rodriguez-Mirasol, J.; Rodriguez, J. J. (Fuel, 2001)
A simple equation based on proxymate analysis (volatile matter and fixed carbon contents) is presented which allows calculation of the higher heating value of lignocellulosic as well as the charcoals resulting from their carbonization. The equation has been tested with different lignocellulosic wastes and chars obtained from carbobization at different temperatures. Derivations from the experimental heating values fall in most cases below 2%. A comparison is presented with some equationsfrom the literature based on proximate, ultimate and chemical analysis data. As a general conclusion the equation proposed in this paper leads to comparableand in many cases more accurate predictions of heating valus and has the advantage of being applicable to a wide range of carbonaceous materials, requiring only a simple, rapid and cheap proximate analysis of the samples
Keywords: charcoal; heating value calculation; lignocellulosics

Fire and late-Holocene expansion of Quercus ilex and Pinus pinaster on Corsica - Carcaillet, Christopher; Barakat, Hala N; Panaïotis, Christophe; Loisel, Roger (Journal of Vegetation Science, 1997)
Abstract. The natural origin of old Quercus ilex (holm oak) forests on the west coast of Corsica is a matter of dispute. This paper discusses the use of pedoanthracology, especially adapted to approach topics in palaeoecology requiring a high spatial precision. It also shows the importance of fire in vegetation change during the Holocene. Pedoanthracology relies on botanical identification and AMS 14C dating of micro-charcoal found in soil. Three test pits were dug in a forest currently protected within the ‘Man and Biosphere’ program. These pits yielded large quantities of charcoal. There is evidence that Pinus nigra ssp. laricio (laricio pine) and understorey heather species (Ericaceae) played an important role in the vegetation at the beginning of the Subatlantic (ca. 2500 BP). The importance of Pinus pinaster (maritime pine), Quercus ilex and a few mesophilic species increased between 2000 and 1000 BP. Charcoal fragments found in the soil show the role of fire in the vegetation changes recorded. The late expansion of P. pinaster results from a high fire frequency. The hypothesis proposed in the paper suggests that fires destroyed the remaining toxic humus that had accumulated during the millennia which preceded the arrival of Q. ilex to our study sites. The late development of holm oak forest is a combination of the migration of the species and the increase of fire frequency since 2500 BP, most probably resulting from slash-and-burn agriculture.
Keywords: charcoal; Evergreen mediterranean forest; Fango valley; human impact; MAB reserve; Quaternary ecology

Fire and late-Holocene expansion of Quercus ilex and Pinus pinaster on Corsica - Carcaillet, Christopher; Barakat, Hala N.; Panaïotis, Christophe; Loisel, Roger (Journal of Vegetation Science, 1997)
Abstract. The natural origin of old Quercus ilex (holm oak) forests on the west coast of Corsica is a matter of dispute. This paper discusses the use of pedoanthracology, especially adapted to approach topics in palaeoecology requiring a high spatial precision. It also shows the importance of fire in vegetation change during the Holocene. Pedoanthracology relies on botanical identification and AMS 14C dating of micro-charcoal found in soil. Three test pits were dug in a forest currently protected within the ‘Man and Biosphere’ program. These pits yielded large quantities of charcoal. There is evidence that Pinus nigra ssp. laricio (laricio pine) and understorey heather species (Ericaceae) played an important role in the vegetation at the beginning of the Subatlantic (ca. 2500 BP). The importance of Pinus pinaster (maritime pine), Quercus ilex and a few mesophilic species increased between 2000 and 1000 BP. Charcoal fragments found in the soil show the role of fire in the vegetation changes recorded. The late expansion of P. pinaster results from a high fire frequency. The hypothesis proposed in the paper suggests that fires destroyed the remaining toxic humus that had accumulated during the millennia which preceded the arrival of Q. ilex to our study sites. The late development of holm oak forest is a combination of the migration of the species and the increase of fire frequency since 2500 BP, most probably resulting from slash-and-burn agriculture.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: charcoal; Evergreen mediterranean forest; Fango valley; human impact; MAB reserve; Quaternary ecology

CHARCOAL ANALYSIS and the VEGETATIONAL EVOLUTION of NORTH-WEST PORTUGAL - FIGUEIRAL, I. (Oxford Journal of Archaeology, 1993)
Summary: The palaeoenvironment of north-west Portugal is investigated from the late Bronze Age to Roman times. This research is based on the analysis of charcoal from seven archaeological sites. the results contain important information for a better understanding of the vegetational environment of man during this period. Man-environment relations are also examined.
APSAPSThe following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: charcoal; paleoecology; Portugal; vegetational environment

CHARCOAL ANALYSIS and the VEGETATIONAL EVOLUTION of NORTH-WEST PORTUGAL - FIGUEIRAL, I (Oxford Journal of Archaeology, 1993)
Summary: The palaeoenvironment of north-west Portugal is investigated from the late Bronze Age to Roman times. This research is based on the analysis of charcoal from seven archaeological sites. the results contain important information for a better understanding of the vegetational environment of man during this period. Man-environment relations are also examined.
APS
Keywords: charcoal; paleoecology; Portugal; vegetational environment

CO2 and steam gasification reactions of a charcoal from holm-oak wood. KINETIC AND TEXTURAL CHARACTERIZATION - Valenzuela Calahorro, C; Bernalte García, M J; Serrano Gómez, V; Bernalte García, A (BIOMASS FOR ENERGY AND INDUSTRY: 5th E.C. Conference, 1990)
In this work are shown the kinetic results of carbon dioxide and steam gasification reactions of a charcoal from holm-oak wood and the evolution of some textural parameters (BET surface area, micropore and mesopore volume) of several activated carbons prepared by such reactions
APS
Keywords: activated carbon; Carbon dioxide; charcoal; Holm oak; kinetic; steam gasification

Pyrolysis of holm-oak wood: influence of temperature and particle size - Figueiredo, J. L.; Valenzuela, C.; Bernalte, A.; Encinar, J. M. (Fuel, 1989)
The pyrolysis of holm-oak wood sawdust was studied to determine the characteristics of the charcoal and the nature and amounts of gases produced. The temperature was varied from 300 to 900 °C and the wood particle size from 0.40 to 2 mm diameter. The fixed carbon content of the charcoal increased with temperature up to 700 °C, and then remained essentially constant. The gases produced were mainly CO, CO2, H2 and CH4. The rate constants and activation energies for the production of each gas were calculated assuming first order kinetics. The composition of the pyrolysis gas produced at each temperature was determined, and its heating value was calculated. Taking into consideration the quality of the charcoal and the heating value of the gases produced, it can be concluded that the optimal pyrolysis temperature is ≈ 600 °C.
Keywords: charcoal; Particle Size; pyrolysis

Pyrolysis of holm-oak wood: influence of temperature and particle size - Figueiredo, J L; Valenzuela, C; Bernalte, A; Encinar, J M (Fuel, 1989)
The pyrolysis of holm-oak wood sawdust was studied to determine the characteristics of the charcoal and the nature and amounts of gases produced. The temperature was varied from 300 to 900 °C and the wood particle size from 0.40 to 2 mm diameter. The fixed carbon content of the charcoal increased with temperature up to 700 °C, and then remained essentially constant. The gases produced were mainly CO, CO2, H2 and CH4. The rate constants and activation energies for the production of each gas were calculated assuming first order kinetics. The composition of the pyrolysis gas produced at each temperature was determined, and its heating value was calculated. Taking into consideration the quality of the charcoal and the heating value of the gases produced, it can be concluded that the optimal pyrolysis temperature is ≈ 600 °C.
Keywords: charcoal; Particle Size; pyrolysis